2023
DOI: 10.5603/pjnns.a2023.0012
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkinetic movement disorders following SARS-CoV-2 infection and vaccination — an update

Abstract: The aim of this review was to summarise current knowledge regarding hyperkinetic movement disorders related to SARS-CoV-2 infection and vaccination in terms of phenomenology, epidemiology, pathogenesis and treatment. After a thorough review of the PubMed and Google Scholar databases (2020-2022), we identified myoclonus and ataxia sometimes accompanied by opsoclonus (AMS) as the two most frequent COVID-19 sequelae, with chorea, tremor and dystonia being very rare. The pathogenesis seems to be variable, but in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, as indicated in the article published in this issue [21], based on the analysis of publications that appeared up until the end of November, 2022, post-COVID-19 parkinsonism is very rare, and the described cases of parkinsonism, being temporally related to COVID-19, seem to have a very diverse aetiology. An analysis of the literature [22] indicates that the most common hyperkinetic movement disorders associated with a history of SARS-CoV-2 infection include myoclonus and ataxia, whereas chorea, tremor and dystonia are extremely rare. Interestingly, hyperkinetic disorders found after COVID-19 seem to have an autoimmune basis and respond well to treatment with glucocorticoids and immunoglobulins [23].…”
mentioning
confidence: 99%
“…However, as indicated in the article published in this issue [21], based on the analysis of publications that appeared up until the end of November, 2022, post-COVID-19 parkinsonism is very rare, and the described cases of parkinsonism, being temporally related to COVID-19, seem to have a very diverse aetiology. An analysis of the literature [22] indicates that the most common hyperkinetic movement disorders associated with a history of SARS-CoV-2 infection include myoclonus and ataxia, whereas chorea, tremor and dystonia are extremely rare. Interestingly, hyperkinetic disorders found after COVID-19 seem to have an autoimmune basis and respond well to treatment with glucocorticoids and immunoglobulins [23].…”
mentioning
confidence: 99%
“…The most reported movement disorder following a COVID infection is myoclonus. [4][5][6] Other commonly reported hyperkinetic movement disorders are ataxia and opsoclonus. 6 Few studies have reported the occurrence of other movement disorders such as blepharospasm and focal dystonia, but they are thought to be fairly rare.…”
mentioning
confidence: 99%
“…[4][5][6] Other commonly reported hyperkinetic movement disorders are ataxia and opsoclonus. 6 Few studies have reported the occurrence of other movement disorders such as blepharospasm and focal dystonia, but they are thought to be fairly rare. 6 Three cases of blepharospasm have been reported with presentation occurring from 2 weeks to 4 months after the onset of symptomatic COVID infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations